Shakespeare as a vehicle for empathy and diagnostic skills training in undergraduate medical students in their psychiatry posting - Pang, Nicholas Tze Ping; Thrichelvam, Nathisha; Wider, Walton (Frontiers in Education, 2023)
Psychiatry undergraduate training has been significantly curtailed by the advent of the COVID-19 pandemic. This article examines the use of Shakespeare’s Hamlet, especially via the characters of Hamlet and Ophelia, to impart two core skills in psychiatry, namely diagnostic abilities and empathy. Medical students undergoing the psychiatry posting watched Kenneth Branagh’s Hamlet online, focusing on identifying psychopathology, forming diagnoses, identifying countertransferences, and developing empathy through acting out close passages. Students were able to identify the features of bipolar disorder in Hamlet, correlating his behaviour with separate depressive and manic episodes. They were also able to appreciate the unique quality of dissociation in Ophelia, especially in Act 4 of Hamlet, and recognise it as a manifestation of post-traumatic stress disorder. Through acting out closed passages, students were also able to feel empathy by putting themselves into the shoes of Hamlet and Ophelia. Such a pedagogical approach has additional unexpected utility in view of the COVID-19 pandemic, which has significantly curtailed face-to-face medical education, leading to alternative online methods such as movies and Shakespearean plays in psychiatry education. In conclusion, though online methods cannot fully supplant face-to-face patient contact, they can be crucial tools in times of necessity and allow students to engage in interdisciplinary education, marrying the arts and the humanities.